RESIDENTS’ SUPPORT FOR COMMUNITY-BASED TOURISM DEVELOPMENT: EVIDENCE FROM MEKONG DELTA, VIETNAM - Pham Cong Danh; Nguyen Minh Huan (HUIT Journal of Science, 2025)
The Mekong Delta provinces are recognized as a destination that possesses the necessary and sufficient conditions to develop community-based tourism effectively. This study explores the mechanisms underlying residents’ support for community-based tourism development by examining the relationships among key latent variables: community involvement, community attachment, perceived benefits, and perceived costs. The study employs a quantitative research approach, utilizing a structured survey distributed to 210 local residents actively involved in community tourism across the Mekong Delta provinces. Data were analyzed using SPSS 22 software to validate the research hypotheses. The results confirm that all hypotheses are supported, providing empirical evidence for the proposed relationships. The findings highlight that perceived benefits and community involvement have the most significant influence on residents’ support for tourism development. Furthermore, perceived benefits and costs serve as critical mediators, linking community attachment and involvement to support for tourism development. Based on the findings, the study proposes actionable solutions to enhance local participation in community tourism and foster the sustainable development of tourism in the region. These include solutions related to local human resource development, management policies, the diversification of local tourism products, and strategies for promoting and marketing tourism offerings effectively.